Needs Analysis for Teaching English at The International Relation Study Program University of Mataram - Lusy Yohanes Duka; I Made Sujana; Boniesta Zulandha Melanie (Indonesian Journal of Teacher Education, 2020)
The purpose of this study is to: (a) Find out the students level of English at The International Relation Study Program. (b) Find out the needs of English perceived by the students at The International Relation Study Program. (c) Find out The needs of English perceived by English lecturer and subject specialist at The International Relation Study Program. (d). Make recommendations for teaching English at non-English Study Program at The International Relation Study Program. The method used in this study is descriptive method. This research is conducted at The International Relation Study Program, The University of Mataram and determined by purposive sampling. The unit analysis in this study is the students with a total of 43 and the lecturers with a total of 2. Based on the research that has been done, it can be concluded as follows: (a) The initial level ability of students that have been measured using the ECSCS Placement Test is known that the initial ability of students are in Pre-Intermediate level with an average score of 73.06. (b) The need of English is perceived by the students at The International Relation Study Program is to improve the English language skills in terms of speaking actively. (c) The need of English is perceived from the institution, English lecturer and subject specialist can be divided into two categories: short-term goals to prepare the students to be a student and long-term goals to find a job. (d) Based on the results according to the circumstances of students and learning at The International Relation Study Program, then it can be recommended that four courses design with materials and teaching techniques appropriate to the conditions and needs of the students.